Women and Agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
It is estimated that women produce up to 80% of basic foodstuffs, both for household consumption and for sale in sub-Saharan Africa and globally are responsible for half the world?s food production. Despite this, women?s contribution to agriculture is often undervalued or poorly recognised.